Integrated Diagnostics and Theranostics of Thyroid Diseases - Giovanella, Luca (Springer International Publishing : Imprint: Springer, 2023)
This open access book provides basic concepts on Integrated Diagnostics and Theranostics with special emphasis on different human thyroid diseases. Thyroid diseases are increasingly detected (incidentally in many cases) but are clinically negligible in a significant proportion of patients. Accordingly, it is urgent to move from the simple disease detection to a reliable disease characterization in order to concentrate efforts on patients in need of tailored disease management. The current scenario of in vitro and in vivo diagnostics, is fastly moving toward the Integrated Diagnostics (i.e. convergence of imaging, pathology and laboratory tests with advanced information technology). Furthermore, the integration of different information will aid clinicians to properly select treatments and stratify patients' prognosis over time. Theranostics is a perfect paradigm of such integrated approach and radioiodine, indicated for benign and malignant thyroid disease management, was the first and is still the mostly used theranostic agent in medicine. Featuring basics concepts and clinical cases discussions the Atlas will be an invaluable tool for clinicians, laboratory specialists, imaging physicians and biomedical technologists involved in diagnosis and therapy of thyroid diseases.